The spectrum of factor XI deficiency in Italy. (24th September 2013) - Castaman, G.; Giacomelli, S. H.; Caccia, S.; Riccardi, F.; Rossetti, G.; Dragani, A.; Giuffrida, A. C.; Biasoli, C.; Duga, S.
Summary Factor XI (FXI) deficiency is a rare inherited bleeding disorder invariably caused by mutations in the FXI gene. The disorder is rather frequent in Ashkenazi Jews, in whom around 98% of the abnormal alleles is represented by Glu117X and Phe283Leu mutations. A wide heterogeneity of causative mutations has been previously reported in a few FXI deficient patients from Italy. In this article, we enlarge the knowledge on the genetic background of FXI deficiency in Italy. Over 4 years, 22 index cases, eight with severe deficiency and 14 with partial deficiency, have been evaluated. A total of 21 different mutations in 30 disease‐associated alleles were identified, 10 of which were novel. Among them, a novel Asp556Gly dysfunctional mutation was also identified. Glu117X was also detected, as previously reported from other patients in Italy, while again Phe283Leu was not identified. A total of 34 heterozygous relatives were also identified. Bleeding tendency was present in very few cases, being inconsistently related to the severity of FXI deficiency in plasma. In conclusion, at variance with other populations, no single major founder effect is present in Italian patients with FXI deficiency.